2D MXene-derived Nb2O5/C/Nb2C/g-C3N4 heterojunctions for efficient nitrogen photofixation. Issue 17 (30th July 2020) - Jiang, Heyan; Zang, Cuicui; Zhang, Yinglan; Wang, Wenhai; Yang, Chaofen; Sun, Bin; Shen, Yu; Bian, Fengxia
Abstract : Novel 2D MXene-derived Nb2 O5 /C/Nb2 C/g-C3 N4 showed a high nitrogen reduction rate in water (0.365 mmol h −1 gcat −1 ); the nitrogen reduction efficiency could be further promoted 2.5 times (0.927 mmol h −1 gcat −1 ) with the optimized pH of 9. Abstract : Due to the rather high 940.95 kJ mol −1 thermodynamic cleavage energy of the N–N triple bond, developing a robust catalytic process for N2 reduction under mild conditions is a continuing scientific challenge. Here, 2D MXene-derived niobium pentoxide/carbon/niobium carbide/graphite-like carbon nitride (Nb2 O5 /C/Nb2 C/g-C3 N4 ) heterojunctions were explored as photocatalysts for N2 reduction in water. Nb2 O5 /C/Nb2 C/g-C3 N4 heterojunctions were prepared by uniformly growing Nb2 O5 on Nb2 C and then forming g-C3 N4 nanosheets in situ on Nb2 O5 /C/Nb2 C. With an optimized Nb2 O5 /C/Nb2 C : g-C3 N4 ratio of 1 : 1, Nb2 O5 /C/Nb2 C/g-C3 N4 showed a high nitrogen reduction rate (0.365 mmol h −1 gcat −1 ), which was 9.1 times as high as that of the MXene derived Nb2 O5 /g-C3 N4 composite. It is worth mentioning that the enhanced performance of Nb2 O5 /C/Nb2 C/g-C3 N4 should be attributed to the enhancement in photogenerated electron and hole separation efficiency caused by the short-range directional charge transmission over the close contact between Nb2 O5 and conductive Nb2 C as well as the Schottky junction formed at the Nb2 O5 /Nb2 C interface. By further changing the pH of the catalytic system, the concentration of reactive electrons was adjusted and the energy barrier of proton reduction was improved. With the optimized pH of 9 adjusted with NaOH solution, the nitrogen reduction efficiency could be further promoted 2.5 times (0.927 mmol h −1 gcat −1 ).